Shakespeare and Macbeth : the story behind the play - Ross, Stewart; Karpinski, Tony; Ambrus, Victor G. (New York : Viking, 1994)
Tells the story of how Shakespeare conceived and wrote one of his greatest plays. Shows the sources Shakepeare used, the economic worries that plagued the actors who formed the troupe, and the performance being mounted.
Includes index.
Bibliography: p. [45].
3-6
Keywords: Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; Shakespeare, William, -- 1564-1616.; English literature -- History and criticism; English literature -- History and criticism